Bibliometric Analysis of Scopus-Indexed Waqf Studies - Aam Slamet Rusydiana (SMART Insight, 2019)
This study aims to determine the development map of waqf research that is indexed by Scopus. The research was conducted in November 2019 by searching through the Scopus database with the keyword